2013
DOI: 10.1089/jpm.2013.9474
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Palliative Care in Long-Term Care Settings with a Focus on Nursing Homes

Abstract: Almost 1.7 million older Americans live in nursing homes, representing a large proportion of the frailest, most vulnerable elders needing long-term care. In the future, increasing numbers of older adults are expected to spend time and to die in nursing homes. Thus, understanding and addressing the palliative care needs of this population are critical. The goals of this paper are to describe briefly the current state of knowledge about palliative care needs, processes, and outcomes for nursing home residents; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 102 publications
1
43
0
Order By: Relevance
“…The results, however, are consistent with findings in the literature. 5,6 Interview data are also limited as a secondary analysis of data gathered for another purpose. Specific interview questions and follow-up probes regarding the nursing home were not asked; rather these data were in response to questions regarding their experience in care planning with the hospice team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results, however, are consistent with findings in the literature. 5,6 Interview data are also limited as a secondary analysis of data gathered for another purpose. Specific interview questions and follow-up probes regarding the nursing home were not asked; rather these data were in response to questions regarding their experience in care planning with the hospice team.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Two systematic reviews of end-of-life care in nursing homes found challenges in identifying those facing end-of-life, pain management, collaboration with hospice providers, inappropriate hospitalization, lack of advance care planning, unmet family expectations, and communication problems between residents, family, and staff. 5,6 …”
mentioning
confidence: 99%
“…19 In consideration of pursuing these investigations within the HRS, two issues are of particular note relative to the observational design of the HRS. First, the last decade has seen tremendous growth in hospice enrollment among nursing home residents, leading some to call for reduced payments to hospice for these patients.…”
Section: Caregivers and Caregivingmentioning
confidence: 99%
“…Palliative care has been touted by experts as an answer to some of these NH quality concerns. 68 However, formal NH palliative care programs, including specialized training of staff, are scarce. 9 …”
Section: Introductionmentioning
confidence: 99%